Pelayanan Penerbangan Sipil Di Lapangan Udara Darmo Kota Surabaya Tahun 1929-1939 - Zahir Zahir; Arif Akhyat (Pendidikan IPS FKIP ULM, 2023)
Civil aviation activities represent a significant advancement in modern transportation facilities within the city of Surabaya. The purpose of this article is to describe civil aviation services at Darmo Airfield in Surabaya from 1929 to 1939. This research employs historical research methods, including heuristics, source verification, interpretation, and historiography. The sources for this article are primarily derived from a literature study, with primary data collected from various newspapers published between 1929 and 1939. The findings of this study indicate that civil aviation services at Darmo Airfield commenced in 1929. Over the subsequent years, these services expanded to not only cover flight routes within the Dutch East Indies region but also extended to flights to Australia. Additionally, the establishment of civil aviation services facilitated the growth of airmail traffic to and from the city of Surabaya, contributing to the enhanced dynamics of population and goods transportation to and from the city during that period.